Urinary Vitamin D-Binding Protein as a Diagnostic Marker for Diabetic Nephropathy in Type 2 Diabetic Patients: Urinary VDBP in Diabetic Nephropathy - Rasheed, Nadia; Baghdadi, Muhammad Hunain; Sadiq, Fauzia; Hasan, Sajjad Ul; Mehmood, Hafiz Muhammad Khalid (Pakistan Journal of Health Sciences, 2025)
In T2DM (Type 2 Diabetes Mellitus), the most common microvascular complication is DN (Diabetic Nephropathy). Objectives: to explore uVDBP (urinary vitamin D-binding protein) for the detection of DN. Methods: This cross-sectional comparative study was conducted in the Chemical Pathology Department, University of Health Sciences, Lahore. The study individuals were mainly categorized into three groups. Group 1 included normoalbuminuric non diabetic control subjects with normal ACR <30mg/g (n=25). Group 2 included normoalbuminuric T2DM patients with normal ACR <30mg/g (n=25). Group 3 comprised microalbuminuric T2DM patients with raised ACR 30 to 299 mg/g (n=25). Spot urine specimens were collected from T2DM patients. The patients were recruited from the Sheik Zayed Hospital Diabetic Clinic, Lahore. Collected data was analyzed by using SPSS version 24.0. Kruskal-Wallis test, Dunn-Bonferroni post-hoc analysis, and Spearman’s correlation were applied. Results: The findings indicated the Urinary Vitamin D-Binding Protein (uVDBP) level was high in patients with microalbuminuria and normoalbuminuria compared to the control group. Group 3 had the highest median Urinary Vitamin D-Binding Protein (uVDBP) concentration, which was higher than in group 2 and group 1. Among all three groups, there was a statistically significant difference in levels of ACR (Albumin-to-Creatinine Ratio) and urinary Vitamin D-Binding Protein (p value = 0.000). Conclusions. In conclusion, the levels of urinary vitamin-D binding protein are significantly increased in T2DM patients having normoalbuminuria and microalbuminuria compared to non-diabetic control subjects. A significant positive correlation was observed between Urinary Vitamin D-Binding Protein (uVDBP) and albumin creatinine ratio.